In silico Proteomic Analysis Provides Insights Into Phylogenomics and Plant Biomass Deconstruction Potentials of the Tremelalles - Aliyu, Habibu; Gorte, Olga; Zhou, Xinhai; Neumann, Anke; Ochsenreither, Katrin (Frontiers in Bioengineering and Biotechnology, 2020)
Basidiomycetes populate a wide range of ecological niches but unlike ascomycetes, their capabilities to decay plant polymers and their potential for biotechnological approaches receive less attention. Particularly, identification and isolation of CAZymes is of biotechnological relevance and has the potential to improve the cache of currently available commercial enzyme cocktails towards enhanced plant biomass utilization. The order Tremellales comprises phylogenetically diverse fungi living as human pathogens, mycoparasites, saprophytes or associated with insects. Here, we have employed comparative genomics approaches to highlight the phylogenomic relationships among thirty-five Tremellales and to identify putative enzymes of biotechnological interest encoded on their genomes. Evaluation of the predicted proteomes of the thirty-five Tremellales revealed 6,918 putative carbohydrate-active enzymes (CAZYmes) and 7,066 peptidases. Two soil isolates, Saitozyma podzolica DSM 27192 and Cryptococcus sp. JCM 24511, show higher numbers harbouring an average of 317 compared to a range of 267 – 121 CAZYmes for the rest of the strains. Similarly, the proteomes of the two soil isolates along with two plant associated strains contain higher number of peptidases sharing an average of 234 peptidases compared to a range of 226 – 167 for the rest of the strains. Despite these huge differences and the apparent enrichment of these enzymes among the soil isolates, the data revealed a diversity of the various enzyme families that does not reflect specific habitat type. Growth experiment on various carbohydrates to validate the predictions provides support for this view. Overall, the data indicates that the Tremellales could serve as a rich source of both CAZYmes and peptidases with wide range of potential biotechnological relevance.